Covalently immobilized triphenylphosphine rhodium complex: synthesis, characterization, and application in catalytic olefin hydrogenation - Wang, Lei; Jia, Mingjun; Shylesh, Sankaranarayanapillai; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Singh, Anand Pal; Thiel, Werner R. (Chemcatchem, 2010)
A trimethoxysilane functionalized triphenylphosphine was coordinated to rhodium(I) and the resulting rhodium complex was covalently bound to a mesoporous SBA-15 support. The catalytic activity of this hybrid material was studied for the hydrogenation of 2-cyclohexen-1-one and compared with the corresponding homogeneous catalyst. According to the (31)P-MAS NMR data, the catalytically active species was stable against oxidation; no structural change could be detected after exposing it to air for more than two months. Transmission electron microscopy (TEM) measurements on the used catalyst confirmed that the rhodium species was also stable against reduction to the metal because the formation of rhodium nanoparticles during the catalysis could be excluded. The kinetic curves of the recycled system confirmed that this hybrid catalyst shows excellent activity, selectivity, stability, and reusability, and is truly heterogeneous in the hydrogenation reaction.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; mesoporous materials; Rhodium

Covalently anchored ruthenium-phosphine complex on mesoporous organosilica: catalytic applications in hydrogenation reactions - Sisodiya, Sheetal; Lazar, Anish; Shylesh, Sankaranarayanapillai; Wang, Lei; Thiel, Werner R.; Singh, Anand Pal (Catalysis Communications, 2012)
New heterogeneous catalysts for alkene hydrogenation reactions were prepared by the immobilization of trimethoxysilane functionalized triphenylphosphine eta(6)-p-cymene ruthenium complex on mesoporous organosilica (PMO-Ru). Characterization techniques confirmed the structural integrity of the organosilica material and proved the successful anchoring of ruthenium complex. Catalytic activity and stability of PMO-Ru sample investigated in the hydrogenation of various olefins showed higher activity than a neat and MCM-41 supported ruthenium catalyst. High catalytic activity and stability of organosilica supported ruthenium catalyst are attributed to the hydrophobic environments and to the unique structural features imparted from the presence of organic groups in the framewall positions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Heterogenization; Hydrogenation; Organosilica; ruthenium; Triphenyl phosphine

Electrostatic grafting of a triphenylphosphine sulfonate on SBA-15: application in palladium catalyzed hydrogenation - Wang, Lei; Dehe, Daniel; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Zhou, Zhou; Hartmann, Martin; Taylor, Robin N. Klupp; Singh, Anand Pal; Jia, Mingjun; Thiel, Werner R. (Catalysis Science & Technology, 2012)
A novel strategy for the immobilization of a sulfonate functionalized triphenylphosphine ligand by ion-ion interactions on an imidazolium modified SBA-15 is presented. A support containing electrostatically grafted triphenylphosphine as the ligand was reacted with PdCl2( CNPh)(2) and the resulting hybrid material catalyzed olefin hydrogenation under mild conditions. The catalyst exhibits excellent activity, selectivity and stability and it can be reused for at least ten times without any loss of activity. An analogous but covalently grafted palladium system does not show any hydrogenation activity under the same conditions. TEM images of the used catalyst clearly prove the absence of palladium nanoparticles. Additionally, XPS investigations prove that palladium( 0) is formed and the phosphine is oxidized. By AAS no palladium contamination down to 0.5 X 10(-4) mmol could be detected in the products and further leaching tests verified the reaction to be truly heterogeneous. This concept of non-covalent immobilization guarantees a tight bonding of the catalytically active species to the surface in combination with a high mobility, which should be favorable for other catalyses, too.

Disordered mesoporous V/TiO2 system for ambient oxidation of sulfides to sulfoxides - Negi, Sanjay Singh; Sivaranjani, Kumarsrinivasan; Singh, Anand Pal; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2013)
High sulfide conversion and predominant sulfoxide yield has been observed with 0.1% vanadium doped disordered mesoporous Ti1-xVxO2 material at ambient and sub ambient temperatures using environmentally green H2O2 oxidant. Ti1-xVxO2 materials were prepared by one-pot solution combustion method in less than 15 min and thoroughly characterized by X-ray diffraction, HRTEM, Raman spectra and other physicochemical techniques. Different sulfides, such as, phenylsulfide, methyl-p-tolylsulfide, ethylsulfide, thioanisole, were converted into the corresponding sulfoxide. Isolated V5+ incorporated in the TiO2 lattice is likely to be the active species for the sulfide oxidation reaction. Catalyst recycling studies indicates the robustness of the catalyst. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Ambient oxidation; Combustion synthesis; heterogeneous catalysis; Hydrogen peroxide; Mesoporous TiO2; Sulfoxidation; Sulfoxide

Green chemistry approach to styrene from ethylbenzene and air on MnxTi1-xO2 catalyst - Negi, Sanjay Singh; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy; Singh, Anand Pal; Gopinath, Chinnakonda S. (RSC Advances, 2014)
Styrene (ST) is an industrially important commodity chemical, and design of a suitable catalyst, which provides high ethyl benzene (EB) conversion and styrene selectivity at Lower temperature with sustainable activity, is one of the major challenges in the field of heterogeneous catalysis. Manganese incorporated in titania (MnxT1-xO2) anatase Lattice, prepared via the solution combustion method, was evaluated for oxidative dehydrogenation (ODH) of EB with O-2 or air. MnxTi1-xO2 catalysts were characterized by different physiochemical methods. Up to 15% Mn could be introduced into the TiO2 Lattice. TEM and XRD indicate disordered mesoporosity, further confirmed by adsorption isotherm analysis. MnxTi1-xO2 catalysts were evaluated for ST synthesis from EB using air or oxygen as oxidant between 440 and 570 degrees C. Reaction conditions have been varied systematically, such as catalyst composition, and EB/air/O-2 flow. MnxTi1-xO2 shows sustainable 55% styrene yield for 45 h without deactivation under optimum conditions. A thorough analysis of spent catalysts demonstrates the conversion of initial anatase phase MnxTi1-xO2 to Mn3O4 supported on the rutile (R) phase of TiO2. The above change occurs in the first few hours of reaction and the Mn3O4 on R-TiO2 phase is the active phase of the catalyst and responsible for sustainable activity for Longer duration.

Simple, phosphine free, reusable Pd(II)-2,2 `-dihydroxybenzophenone-SBA-15 catalyst for arylation and hydrogenation reactions of alkenes - Lazar, Anish; Vinod, Chathakudath P.; Singh, Anand Pal (New Journal of Chemistry, 2016)
An efficient, simple, phosphine and co-catalyst free C-C coupling reaction heterogeneous catalyst via a post grafting method is developed and reported. A covalently anchored phosphine free Pd(II) based 2,2'-dihydroxybenzophenone (DHBP) complex over organofunctionalized SBA-15 has been synthesized by the reaction between aminofunctionalized SBA-15 (NH(2)SBA-15) and a 2,2'-dihydroxybenzophenone (DHBP) ligand, and further complexation with Pd(II)Cl-2 to get Pd(II)-DHBP@ SBA-15. The synthesized catalysts were characterized by elemental analysis, XRD, N-2 sorption analyses, TG, DTA, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. The synthesized catalysts were screened in arylation (Heck reactions) and hydrogenation reactions of alkenes, and the results show that Pd(II)-DHBP@ SBA-15 exhibits high conversion and selectivity towards arylation and hydrogenation reactions of alkenes with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity.

Efficient olefin epoxidation with high turnover rates over ordered mesoporous silica nanoparticles with uniform manganese sites - Negi, Sanjay Singh; Khatri, Prateek; Singh, Anand Pal (Microporous and Mesoporous Materials, 2023)
Olefin epoxidation has been studied over a series of mesoporous manganese silicate nanoparticles and tBuOOH. Partial substitution of Si by Mn in silica framework leads to highly dispersed, distorted Mn(III) sites, confirmed by various physicochemical analyses. High conversion and stable styrene oxide, stilbene oxide and epoxy cyclohexane yield have been achieved with MS75 with 1:1.5 ratio of olefin: oxidant. However, at faster reaction rates lower styrene oxide yield is observed at lower Mn-containing catalyst (MS100). High TON, TOF over manganese sites shows accessible monomeric Mn sites. Attributed to high reactant density at redox-active Mn silicate sites due to facile diffusion across shallow pore depth channels of nanoparticulate om-MSx and surface hydrophobic characteristics. The catalysts were found to be stable under recycling and filtration experiments. The excellent stability against leaching of active manganese species indicates stable sites and good textural properties in om-MSx, essential for extended activity.
Keywords: epoxidation; Manganese silicates; Mesoporous silica nanoparticles; Ordered mesoporous silica; pH adjustment